The Effect of Grain Size and Temperature (77 to 293 K) on the Limiting Displacements During the Shearing of Carbon Steels - S. Dzidowski (Engineering Transactions)
The effect of grain size on the limiting displacements due to localization of strains during shearing is described. Tests on carbon steels of 0.09 and 0.44% C content sheared at the temperature from 77 to 293 K were carried out. It has been found that the lowering of the temperature of shearing speeds up localization of strains, particularly at tower carbon contents in steel. As the temperature was lowered, a progressive decline in the influence of carbon content on the value of limiting displacements was observed. Refinement of structure delayed localization of strains in a manner practically independent of temperature. A general form of an equation which describes the simultaneous effect of temperature, grain size and carbon content on the limiting displacements of the material in the plane of shearing has been proposed.